Use of Virtual Reality Technology for Learning Mechanical Skills - Anto Susilo; Ling Barra; Yuanyuan Wang (Journal of Computer Science Advancements, 2024)
Background: With the technological landscape in education shifting rapidly, Virtual Reality presents a novel approach to practical skill development, particularly in mechanical engineering. This study explores the potential of Virtual Reality to enhance the learning of specific mechanical skills, such as Mechanical Skills, which are crucial in the increasingly automated industry. The main objective of this research was to assess the effectiveness of Virtual Reality technology in teaching mechanical skills compared to traditional hands-on methods. The study employed a quasi-experimental design involving 100 mechanical engineering students from two universities. Using conventional training methods, which included [insert specific methods], participants were randomly assigned to a VIRTUAL REALITY training group and a control group. Both groups were tested on their ability to perform specific mechanical tasks, such as [insert specific tasks], before and after the training sessions. The Virtual Reality group demonstrated a statistically significant improvement in performance accuracy and speed compared to the control group. Post-study surveys also indicated higher satisfaction and engagement levels among the Virtual Reality group. The findings suggest that Virtual Reality technology can significantly enhance the learning of mechanical skills, offering a more effective and engaging approach than traditional methods. The potential of Virtual Reality to revolutionize mechanical engineering education is inspiring, offering a new and exciting way to teach and acquire practical skills.